2018
DOI: 10.3892/ol.2018.8564
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of hsa‑miR‑125a‑5p enhances proliferation, migration and invasion of head and neck squamous cell carcinoma cell lines by upregulating C‑C chemokine receptor type�7

Abstract: Head and neck squamous cell carcinoma (HNSCC) is usually diagnosed accompanied by lymph node metastasis. C-C chemokine receptor type 7 (CCR7) is associated with the invasion and metastasis of tumors in HNSCC through various signaling pathways. The role of hsa-miR-125a-5p in HNSCC remains unclear. The present study was performed to investigate the association between hsa-miR-125a-5p and CCR7 in HNSCC. Reverse transcription-quantitative polymerase chain reaction was applied to analyze the expression of hsa-miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“… 26 As for hsa-miR-125b, a previous study reported overexpression of hsa-miR-125b significantly enhanced the ability of cell proliferation, migration, and invasion in Head and Neck Squamous Cell Carcinoma, with upregulation of C-C Chemokine Receptor Type 7. 27 It also activates p53 and Induces Apoptosis in Lung Cancer Cells. 28 Besides, hsa-miR-125b may act as a cancer suppressor by regulating the BRCA1 signaling, and reintroduction of hsa-miR-125b analogs could be a potential adjunct treatment for advanced/chemoresistant breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 26 As for hsa-miR-125b, a previous study reported overexpression of hsa-miR-125b significantly enhanced the ability of cell proliferation, migration, and invasion in Head and Neck Squamous Cell Carcinoma, with upregulation of C-C Chemokine Receptor Type 7. 27 It also activates p53 and Induces Apoptosis in Lung Cancer Cells. 28 Besides, hsa-miR-125b may act as a cancer suppressor by regulating the BRCA1 signaling, and reintroduction of hsa-miR-125b analogs could be a potential adjunct treatment for advanced/chemoresistant breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…miR-125a-5p, an extensively studied miRNA in tumors, has been identified to serve an inhibitor role in hepatitis B virus-related hepatocellular carcinoma (15). Jin et al (24) suggested that miR-125a-5p is associated with the clinical stages of head and neck squamous cell carcinoma, and the expression levels in low tumor stages (stages I and II) were higher compared with that in the high stages (stages III and IV). Furthermore, miR-125a-5p is a potential biomarker for acute ischemic stroke (25).…”
Section: Discussionmentioning
confidence: 99%
“…High hsa-miR-107 expression was associated with poor clinicopathological parameters and prognosis in pancreatic ductal adenocarcinoma patients [53]. On the other hand, overexpression of hsa-miR-125a-5p significantly enhanced the ability of cell proliferation, migration and invasion in HNSCC, hsa-miR-125a-5p [54]. The hsa-miR-125a-5p induced apoptosis via a p53dependent pathway in human lung cancer cells [55].…”
Section: External Validation Of Survival Markers Using On Another 23 Cancersmentioning
confidence: 96%